Hemodialysis (HD) Duration is Associated with The Quality of Life of Patients with Kidney Failure Undergoing Hemodialysis - Arifin Hidayat; Frana Andrianur; Dwi Prihatin Era; Hesti Prawita Widiastuti (Jurnal Kesehatan, 2025)
Hemodialysis is an early procedure that can quickly save the lives of patients with end-stage renal disease. Various studies show inconsistent results for several factors related to sociodemographics, such as age, gender, education, occupation, and income. Hemoglobin levels and hemodialysis access are rarely discussed, and the length of undergoing hemodialysis is rarely discussed. Therefore, this study investigates the variables related to the quality of life of chronic renal failure patients receiving hemodialysis. This study is a descriptive correlational study using a cross-sectional design. Purposive sampling was conducted with 60 chronic renal failure patients undergoing hemodialysis from July to October 2023 at Abdul Wahab Sjahranie Regional General Hospital, Samarinda. This research instrument uses a questionnaire; the first part is a fill-in sheet that includes (age, gender, education, occupation, income, length of hemodialysis, hemoglobin (HB) level, and hemodialysis access (HD). The second component is an instrument used by researchers to assess the patient's quality of life, the WHOQoL instrument. The logistic regression test was utilized in the statistical analysis. The length of hemodialysis is the most dominant factor in the quality of life of patients with kidney failure undergoing hemodialysis (p-value=0.029, with Odd-Ratio (OR)=10.86, 95%CI=1.282-92.036). The results of this study indicate that the length of hemodialysis is the most dominant factor in the patient's quality of life. Thus, it is important to make educational efforts and provide assistance to family and peer nurses during hemodialysis to prevent the emergence of negative thoughts that worsen the quality of life for patients.